The promotion of decent and sustainable employment in cooperatives and labor societies - Canalda Criado, Sergio (REVESCO. Revista de Estudios Cooperativos, 2019)
The promotion of the social economy and the pursuit of full employment by public authorities should promote the creation of stable and quality employment. In this context, employment policies must be targeted at the incorporation of members in cooperatives and workerowned companies. The creation of employment as a result of the intervention of the public powers can be assessed quantitatively, taking into account the number of jobs created through employment policies. However, this paper focuses on the type of employment in qualitative terms, studying the beneficiary entities, the social groups whose access to membership is granted, and the selection criteria and the obligations assumed by beneficiaries.